Comprehending irony in text: evidence from scanpaths - Olkoniemi Henri; Mézière Diane; Kaakinen Johanna K. (Taylor & Francis, 2025)
Eyetracking studies have shown that readers reread ironic phrases when resolving their meaning. Moreover, it has been shown that the timecourse of processing ironic meaning is affected by reader’s working memory capacity (WMC). Irony is a context-dependent phenomenon but using traditional eye-movement measures it is difficult to analyze processing beyond sentence-level. A promising method to study individual differences in irony processing at the paragraph-level is scanpath analysis. In the present experiment, we analyzed whether individual differences in WMC are reflected in scanpaths during reading ironic stories by combining data from two previous eye-tracking studies (N = 120). The results revealed three different reading patterns: fast-and-linear reading, selective reading, and nonselective rereading. The readers predominantly used the fast-and-linear reading pattern for ironic and literal stories. However, readers were less likely to use the nonselective rereading pattern with ironic than literal texts. The reading patterns for ironic stories were modulated by WMC. Results showed that scanpaths captured differences missed by standard measures, showing it to be a valuable tool to study individual differences in irony processing.